Помогите, срочно, пожалуйста!!)) 3sin^2x - 7 sinxcosx + 6 cos^2x = 1

0 голосов
49 просмотров

Помогите, срочно, пожалуйста!!)) 3sin^2x - 7 sinxcosx + 6 cos^2x = 1


Алгебра (707 баллов) | 49 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

3sin^2x-7sinxcosx+6cos^2x=1 \\ 2sin^2x-7sinxcosx+5cos^2x=0 \\ \\ \left \{ {{2tg^2x-7tgx+5=0} \atop {cos^2x\neq0}} \right \\ \\ tgx=t \\ 2t^2-7t+5=0 \\ D=(-7)^2-4*2*5=49-40=9=3^2 \\ \\ t_1=\frac{7+3}{2*2}=2,5\ \ \ \ \ \ \ \ \ \ \ \ t_2=\frac{7-3}{2*2}=1 \\ \\ tgx=2,5 \\ \\ x_1=arctg(2,5)+\pi n,\ \ \ \ \ \ n \in Z \\ \\ tgx=1 \\ \\ x_2=\frac{\pi}{4}+\pi n,\ \ \ \ \ \ n \in Z

 

Ответ: x_1=arctg(2,5)+\pi n \\ \\ x_2=\frac{\pi}{4}+\pi n,\ \ \ \ \ \ n \in Z

(16.1k баллов)
0 голосов

3sin^2x - 7 sinxcosx + 6 cos^2x = 1

 

3sin^2x-7sinxcosx+ 6cos^2x=sin^2x+cos^2x 

2sin^2x-7sinx*cosx+5cos^2x=0

2sin^2x-7sinx*cosx=-5cos^2x  поделим на кос квадрат

2tg^2x-7tgx=-5 

tgx= t

2t^2-7t+5=0

D=49-4*2*5=V9=3

 

t=7+3/6=10/6=5/3

t2=7-3/6=4/6=2/3

tgx=5/3

x=arctg(5/3)+pi*k

x=arctg(2/3)+pi*k

можно перевести на синус 

(224k баллов)